2011
DOI: 10.1097/jsa.0b013e3181ec8707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Combined Single Photon Emission Computerized Tomography and Conventional Computer Tomography (SPECT/CT) in Sports Medicine

Abstract: Integrated hybrid single photon emission computerized tomography (SPECT)/computer tomography (CT) is a promising new diagnostic imaging modality for orthopedic patients. A high diagnostic yield is available from combining the detection of abnormal bone metabolism with SPECT, to the precise anatomical detail available in high resolution CT. With this review, we endeavor to illustrate the clinical value and future perspectives of SPECT/CT in sports medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 19 publications
0
50
0
1
Order By: Relevance
“…In our own work, we have demonstrated that SPECT/CT is able to detect symptomatic bipartite patella in patients with knee problems (Hirschmann et al 2011b ). In the case presented here, the patient, who is a world-class downhill skier, suffered from osteoarthritis of the fabellar bone in his knee, which was unambiguously identifi ed.…”
Section: Accessory Bonesmentioning
confidence: 96%
See 1 more Smart Citation
“…In our own work, we have demonstrated that SPECT/CT is able to detect symptomatic bipartite patella in patients with knee problems (Hirschmann et al 2011b ). In the case presented here, the patient, who is a world-class downhill skier, suffered from osteoarthritis of the fabellar bone in his knee, which was unambiguously identifi ed.…”
Section: Accessory Bonesmentioning
confidence: 96%
“…The most common accessory bones of the knee are the fabella and bi-or multipartite patella (Hirschmann et al 2011b ). In our own work, we have demonstrated that SPECT/CT is able to detect symptomatic bipartite patella in patients with knee problems (Hirschmann et al 2011b ).…”
Section: Accessory Bonesmentioning
confidence: 98%
“…With SPECT-CT, we are able to interpret subtle, vague abnormalities on bone scans as specifi c focal areas of pathology. SPECT-CT has provided new indications for bone scintigraphy and is increasingly recognized as a promising diagnostic tool in orthopedic conditions (Scharf 2009 ) and sports injuries (Hirschmann et al 2011 ), especially in complex bony structures as the foot and ankle. Recently, hybrid systems capable of acquiring high-resolution multislice CT images have been developed, which will further increase the diagnostic accuracy ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…SPECT/CT allows accurate anatomical localisation of metabolic tracer activity [9]. Recently, we have introduced a novel diagnostic SPECT/CT algorithm for the challenging group of patients with problems after ACL reconstruction [6,9,14,15]. This standardised algorithm including grading and anatomical localization of SPECT/CT tracer uptake promises the identification of specific pathological tracer uptake patterns and distributions [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity and distribution of 99mTc-HDP-SPECT/ CT tracer, which as diphosphonate is targeted towards osteoblastic activity, is influenced by mechanical or anatomical alignment, vascular supply, infection, osteoblastic activity or currently unknown other factors [9,13,14,[16][17][18][19]. In patients after ACL reconstruction it could be hypothesized if the position and orientation of the bone tunnels and the stability and/or laxity of the knee joint are decisive factors.…”
Section: Introductionmentioning
confidence: 99%